2020
DOI: 10.1007/s13197-020-04744-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal and non-thermal processing on astringency reduction and nutrient retention in cashew apple fruit and its juice

Abstract: The present study is aimed at evaluating the effect of different processing techniques on astringency reduction, nutrient retention, and sensory attributes in cashew apple fruit and its juice. Astringency attribute was measured by tannin content, while nutrition profile by ascorbic acid, total sugars, and antioxidant activity. Hot water, steaming, and microwave were selected as the source of heat application for treating whole fruit, where the process variables were the temperature and exposure time. The non-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…The juice obtained by pressing the crushed material was filtered through a 0.5 mm mesh sieve. Finally, the different juices were stored for sixteen (16) days in the refrigerator (Fiocchetti, Mazzara, Italy) at 4˚C [19].…”
Section: Juice Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The juice obtained by pressing the crushed material was filtered through a 0.5 mm mesh sieve. Finally, the different juices were stored for sixteen (16) days in the refrigerator (Fiocchetti, Mazzara, Italy) at 4˚C [19].…”
Section: Juice Preparationmentioning
confidence: 99%
“…Despite many advantages, not all of the many technologies studied in these different studies are accessible and not adopted by processors due to the lack of financial means to access these sophisticated technologies. In order to propose low-cost and accessible solutions, a study on the effect of heat and non-heat treatment on the reduction of astringency and nutrient retention in cashew apple fruit and juice was conducted [16]. In this study the different techniques resulted in the retention of high concentrations of ascorbic acid, total sugar and antioxidant activity, making it an excellent option for the mixed juice beverage market.…”
Section: Introductionmentioning
confidence: 99%
“…48 Methods such as blanching, addition of gelatin, fermentation, removal of fruit skin, addition of tannase, hydrothermal processing, centrifugation and microfiltration, and natural coagulants (such as okra pod) have been identified as effective ways of reducing the tannin content to appreciable levels. 45,[49][50][51][52][53] Other organic acids like citric, malic, and acetic acid that mediate a lot of physiological functions are also in abundance in the cashew apple. 16 The variations in the nutritional composition of the cashew apple are influenced by variety, soil quality, environmental conditions (climate), agronomic practices, maturity stage of the fruits, and processing conditions.…”
Section: Nutritional Composition Of Cashew Applementioning
confidence: 99%
“…Microwave is a cleaner and greener energy resource to drive the chemical reactions, and it has advantages in terms of extraordinary efficiency and high yield. The applications of microwave in chemical reactions are very wide, such as organic synthesis, biomass treatment, and nanomaterials. Most accelerating chemical reactions under the microwave irradiation can be explained by the microwave thermal effect. , Numerous experimental studies determine that not only the microwave thermal effect but also the microwave nonthermal effect play a decisive role in enhancing chemical reactions. Tiwari et al demonstrated the simultaneous activation of CH 4 and N 2 in a microwave catalytic reaction to produce NH 3 and C 2 products and found that the elementary reaction steps leading to NH 3 synthesis occurs due to the nonthermal effects of microwave irradiation. Silva et al verified that the combination of thermal and nonthermal effects during the microwave-assisted hydrothermal treatment provides ideal conditions for an efficient and rapid synthesis of pristine SrTiO 3 mesocrystals.…”
Section: Introductionmentioning
confidence: 99%